(untitled) (Biuletyn Kryminologiczny, 2021)
The aim of the paper is to present selected results of the analysis of the impact of migration policies in the context of development of such criminal phenomena as organising irregular migration or document fraud linked to it. One of the elements of the analysis was the identification of mechanisms of formal social control in reference to the example of functioning of a simplified system aimed at controlling foreigners’ access to the labour market in Poland. In practice, the system has brought also consequences in the form of breaches of penal law. Paradoxically, in the Polish case not more restrictions, but simplifications in the area of foreigners’ access to the labour market have determined in recent years the landscape of irregular migration. Due to the characterof the recognised (administrative or penal) law infringements, the phenomenon may be rather called semi-legal or half-legal migration, since its specificity is the apparent compliance with the laws on entry, stay or work of foreigners, and the simplified procedure of admitting foreigners to the labour market can be helpful in this respect. However, more in-depth reflection allows for identification of law infringements within these actions, which may stem from ambiguous or incomplete legal norms. The differences in perceptions of the abuses of the simplified system of employing foreigners and in responses to them identified in the qualitative study lead to the conclusion that formal social control sometimes contributes to the development of negative phenomena, although the expected result of it is preventing them. Celem artykułu jest przedstawienie wybranych wniosków z analizy skutków polityki migracyjnej w kontekście rozwoju takich zjawisk przestępczych jak organizowanie nielegalnej migracji oraz związane z tym fałszowanie i wyłudzanie dokumentów. Jednym z elementów analizy była identyfikacja mechanizmów formalnej kontroli społecznej na przykładzie funkcjonowania uproszczonej procedury dopuszczania cudzoziemców do rynku pracy w Polsce. System ten w praktyce przyniósł też skutki w postaci naruszeń prawa karnego. Paradoksalnie, w polskich warunkach to nie większe restrykcje, ale ułatwienia w zakresie dostępu cudzoziemców do rynku pracy determinowały w ostatnich latach obraz nielegalnej migracji. Z uwagi na charakter obserwowanych naruszeń prawa (administracyjnego i karnego) zjawiska te można nazywać raczej quasi-nielegalną czy półlegalną migracją, gdyż jej cechą charakterystyczną jest pozorne przestrzeganie zasad wjazdu, pobytu czy pracy cudzoziemców, czemu służyć może właśnie uproszczony system dostępu cudzoziemców do rynku pracy. Pogłębiona refleksja pozwala jednak na identyfikację naruszeń prawa w ramach tych działań, czemu sprzyjają niejednoznaczne czy niekompletne normy prawne. Zidentyfikowane w badaniu jakościowym różnice w postrzeganiu nadużyć uproszczonego systemu zatrudniania cudzoziemców i w reagowaniu na nie prowadzą do wniosku, że formalna kontrola społeczna przyczynia się czasem do rozwoju negatywnych zjawisk, mimo że jej spodziewanym rezultatem jest zapobieganie im.